Black site : the CIA in the post-9/11 world - Mudd, Philip 2013 (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2019)
"A bold account of one of the most controversial and haunting initiatives in American history, [this book] tells the full story of the post-9/11 counterterrorism world at the CIA. When the towers fell on September 11, 2001, nowhere were the reverberations more powerfully felt than at CIA headquarters in Langley, Virginia. Almost overnight, the intelligence organization evolved into a war-fighting intelligence service, constructing what was known internally as 'the Program': a web of top-secret detention facilities intended to help prevent future attacks on American soil and around the world. With [this book], former deputy director of the CIA Counterterrorist Center Philip Mudd presents a full, never-before-told story of this now-controversial program, directly addressing how far America went to pursue al-Qa'ida and prevent another catastrophe.^